2015
DOI: 10.2106/jbjs.n.00947
|View full text |Cite
|
Sign up to set email alerts
|

MRI for the Evaluation of Knee Pain

Abstract: MRI utilization by orthopaedic surgeons results in more appropriate interventions for patients with symptoms and findings most amenable to surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 1 publication
3
17
0
1
Order By: Relevance
“…Debaters against GP direct access MRI pathways often identify situations where GPs lack dedicated pre-use training and quality assurance, and operate within an unlimited condition open access environment, factors which are critical to success. 10,24 These studies contrast with findings from The Netherlands, indicating changes in GP referral patterns following MRI referrals. 25 Roberts et al 24 admit to the value of an educational primer as testament to effectiveness of careful clinical evaluation and prudent MRI use.…”
Section: Comparison With Existing Literaturementioning
confidence: 61%
See 2 more Smart Citations
“…Debaters against GP direct access MRI pathways often identify situations where GPs lack dedicated pre-use training and quality assurance, and operate within an unlimited condition open access environment, factors which are critical to success. 10,24 These studies contrast with findings from The Netherlands, indicating changes in GP referral patterns following MRI referrals. 25 Roberts et al 24 admit to the value of an educational primer as testament to effectiveness of careful clinical evaluation and prudent MRI use.…”
Section: Comparison With Existing Literaturementioning
confidence: 61%
“…10,24 These studies contrast with findings from The Netherlands, indicating changes in GP referral patterns following MRI referrals. 25 Roberts et al 24 admit to the value of an educational primer as testament to effectiveness of careful clinical evaluation and prudent MRI use. Other studies support educational interventions and patient pre-selection as means of preventing increases in GP referral rates.…”
Section: Comparison With Existing Literaturementioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, some authors suggest that an MRI examination prior to the planned arthroscopic surgery does not change the treatment strategy [19]. The findings are supported by other researchers [49], however, if the MRI is ordered by an orthopaedic surgeon, it has a greater impact on the planned treatment [50] compared to a primary care physician. The accurate referral may incline the usage of cartilage dedicated sequences, which improves the overall diagnostic accuracy [51].…”
Section: Discussionmentioning
confidence: 81%
“…Researchers demonstrated that MRI studies that were ordered by orthopedic surgeons versus non-orthopedic physicians were more likely to be associated with a specific diagnosis, impact patient treatment, and result in surgery that was of benefit to the patient. 9,10,12 Additionally, when used as a screening tool for non-specific hip pain, Keeney et al calculated a cumulative institutional cost for obtaining a single study that impacted a patient’s treatment of $59,296. When the study cost was compared between providers, they found that the cost of obtaining a study that impacted a patient’s treatment was three-times greater when the ordering physician was a non-orthopedic provider ($7,804 versus $2,834) suggesting that education of referring physicians is paramount to reducing healthcare costs.…”
mentioning
confidence: 99%